(untitled) (Development Service Industry Management, 2025)
The article substantiates the need to change traditional approaches to ensuring motivation and stimulating work and taking into account aspects of personal professional development of personnel, where preference is given to improving flexibility, innovation, adaptability and other necessary features of effective employment to create an attractive working environment in which it is possible to establish highly productive work. It is emphasized that the use of creative management is critically necessary for solving complex tasks of the enterprise when implementing new and promising projects, where personnel need to demonstrate a high level of intellectualization of work, professional skills, new competencies, etc. The architecture of developing a program for increasing motivation and improving material stimulation of personnel in accordance with the aspects of creative management is determined. It is concluded that creative management should be implemented in all vectors of increasing motivation and improving material stimulation of personnel, since traditional methods of encouragement are gradually losing their effectiveness in the modern dynamic business environment. According to these assumptions, vectors for increasing motivation and improving material incentives for personnel when implementing creative management at the enterprise are proposed. It is emphasized that creative management focuses on the development of such qualities as flexibility, the ability to adapt to changes, which in turn improves employees ability to find non-standard solutions and effectively solve complex tasks. Creative management acts as a key element in the system of motivation and material incentives for personnel, providing conditions for the development of the creative potential of employees and achieving high results of the enterprise’s activities.